2015
DOI: 10.1002/chem.201503171
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Organocatalyzed Rearrangement of Propargyl Vinyl Ethers to Salicylaldehyde Derivatives: An Experimental and Theoretical Study

Abstract: The microwave-assisted imidazole-catalyzed transformation of propargyl vinyl ethers (PVEs) into multisubstituted salicylaldehydes is described. The reaction is instrumentally simple, scalable, and tolerates a diverse degree of substitution at the propargylic position of the starting PVE. The generated salicylaldehyde motifs incorporate a broad range of topologies, spanning from simple aromatic monocycles to complex fused polycyclic systems. The reaction is highly regioselective and takes place under symmetry-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…Most of the cited methodologies required dry conditions, high temperatures, or pre‐activation of the reagents. Nevertheless, noticeable progress has been made by using trifluoroacetic anhydride (TFAA) or trifluoroacetic acid/trifluoroacetic anhydride (TFA/TFAA), under mild heating conditions and air moisture, to allow the S E Ar of activated and non‐strong deactivated benzoic acids, depending on the nucleophilic strength of the aromatic compound.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the cited methodologies required dry conditions, high temperatures, or pre‐activation of the reagents. Nevertheless, noticeable progress has been made by using trifluoroacetic anhydride (TFAA) or trifluoroacetic acid/trifluoroacetic anhydride (TFA/TFAA), under mild heating conditions and air moisture, to allow the S E Ar of activated and non‐strong deactivated benzoic acids, depending on the nucleophilic strength of the aromatic compound.…”
Section: Introductionmentioning
confidence: 99%
“…These PVEs are easily accessible from ketones, through a two‐step procedure entailing: 1) generation of the tertiary propargylic alcohol, and 2) transformation of the alcohol into the corresponding β‐alkoxy‐acrylate derivative 6 . We have also shown that the microwave irradiation of these tertiary PVEs 6 in the presence of catalytic amounts of imidazole generates salicylaldehyde derivatives 8 through an all‐pericyclic domino process (Scheme c) . During these studies, we discovered that this process could be funneled toward the formation of trisubstituted 2HPCs 7 by a careful control of the temperature.…”
Section: Resultsmentioning
confidence: 91%
“…The propargyl vinyl ethers were prepared according to our previous experimental procedure (see below for a general procedure). Products 6a , 6e ,[18a] 6h , 6i 6j 6k ,[18b] 6l ,[18b] 6m , 6q ,[18b] 6r ,[18a] 6t ,[18a] 6u ,[18a] 7a , 7r ,[18a] and 18 have been described previously.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol delivered 2HP structures endowed with different topologies, including monocycles ( 53 - mc ), 2,2-spiro-bicycles ( 53 - sbc ), and 2,2-spiro-macrobicycles ( 53 - smbc ). The main limitation arose from the presence of a t Bu substituent at the alkyne position (R 1 ): In this case, the reaction followed a different pathway through a sequential [1,7]- H shift/6π-electrocyclization/MeOH elimination set of reactions [54].…”
Section: Synthesis Of the 2hp Corementioning
confidence: 99%